The Effect of Strategic Planning and Green Finance on BUMDes Sustainability Performance with Human Resource Competence and Innovation Capability as Moderating Variables. - Saputri, Reza Septiana; Basri, Yesi Mutia (Universitas Riau, 2026)
This study examines the effects of strategic planning and green finance on the sustainability performance of Village-Owned Enterprises (BUMDes) in Kuantan Singingi Regency, with human resource competence and innovation capability as moderating variables. While prior research highlights the role of strategic planning and green finance in organizational sustainability, empirical evidence in village-based enterprises remains limited and often overlooks internal capabilities as contingency factors. Grounded in Resource-Based Theory and aligned with the Village Sustainable Development Goals (SDGs)—covering economic, social, and environmental dimensions—this study adopts a quantitative survey approach. Data were collected from 155 active BUMDes managers and supervisors out of 218 units and analyzed using SEM-PLS. The results show that strategic planning and green finance positively and significantly enhance sustainability performance. Human resource competence strengthens the impact of strategic planning but weakens the effect of green finance, while innovation capability does not moderate these relationships. The findings contribute theoretically by refining the application of Resource-Based Theory in village enterprises and empirically by proposing a contextual sustainability framework for improving BUMDes management performance.